DAGLα Inhibition as a Non-invasive and Translational Model of Episodic Headache - Levine, Aidan; Liktor-Busa, Erika; Karlage, Kelly L.; Giancotti, Luigi; Salvemini, Daniela; Vanderah, Todd W.; Largent-Milnes, Tally M. (Frontiers in Pharmacology, 2021)
Recent findings suggested that Clinical Endocannabinoid Deficiency underlies the pathophysiology of pain disorders, including migraine and headache. In models of medication overuse headache induced by sustained administration of sumatriptan or morphine, 2-AG levels were selectively depleted in the periaqueductal grey (PAG) and anandamide (AEA) increased in the cortex suggesting distinct regulation of the endocannabinoid system during headache pain. These results led to the hypothesis that blockade of DAGL, to reduce 2-AG levels would induce headache-like behaviors as a new, translationally relevant model of episodic headache. Our study investigated whether non-selective and selective blockade of DAGL, the main biosynthetic enzyme for 2-AG, induced periorbital and hind-paw allodynia, photophobia, anxiety-like behaviors, responsivity to abortive anti-migraine agents, and 2-AG/AEA levels. Injection of non-selective DAGL (DH376, 10 mg/kg, IP) and selective DAGLα (LEI106, 20 mg/kg, IP) inhibitors, but not DAGLβ agents, induced facial sensitivity in 100% and ~60% of female and male rats, respectively, without induction of peripheral sensitivity. Notably, male rats showed significantly less sensitivity than female rats after DAGLα inhibition, suggesting sexual dimorphism in this mechanism. Importantly, LEI106 induced periorbital allodynia was attenuated by administration of the clinically available abortive antimigraine agents, sumatriptan and olcegepant. Selective DAGLα inhibition induced significant photophobia as measured by the light-dark box, without anxiety like behaviors or changes in voluntary movement. Analysis of AEA and 2-AG levels at the time of peak pain sensitivity revealed reductions in 2-AG in the visual cortex and periaqueductal grey (PAG), without altering anandamide or significantly increasing diacylglycerol levels. These results provide foundational evidence for DAGL-2AG in the induction of headache-like pain and photophobia without extracephalic allodynia, thus modeling the clinical episodic migraine. Mechanistically, behavioral measures of headache sensitivity after DAGL inhibition suggests that reduced 2-AG signaling in the cortex and PAG, but not the trigeminal nucleus caudalis or trigeminal ganglia, drives headache initiation. Therefore, episodic DAGL inhibition, which reduces the time, cost, and invasiveness of currently accepted models of headache, may fill the need for episodic migraine/headache models mirroring clinical presentation. Moreover, use of this approach may provide an avenue to study the transition from episodic to chronic headache.